2020
DOI: 10.1007/s00431-020-03728-y
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating peak inspiratory pressures and tidal volume in premature neonates on NAVA ventilation

Abstract: Neurally adjusted ventilatory assist (NAVA) ventilation allows patients to determine their peak inspiratory pressure and tidal volume on a breath-by-breath basis. Apprehension exists about premature neonates' ability to self-regulate breath size. This study describes peak pressure and tidal volume distribution of neonates on NAVA and non-invasive NAVA. This is a retrospective study of stored ventilator data with exploratory analysis. Summary statistics were calculated. Distributional assessment of peak pressur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 44 publications
0
12
0
Order By: Relevance
“…Together with recent data published by our group, this study supports the suggestion that preterm infants exhibit functional maturity of respiratory control and have sufficient feedback mechanisms, allowing NAVA ventilation. 29,31 Most infants were switched to NAVA already on their first day of life; however, the median number of NAVA ventilation episodes was three, meaning that most of the infants also needed other invasive respiratory modes.…”
Section: Discussionmentioning
confidence: 99%
“…Together with recent data published by our group, this study supports the suggestion that preterm infants exhibit functional maturity of respiratory control and have sufficient feedback mechanisms, allowing NAVA ventilation. 29,31 Most infants were switched to NAVA already on their first day of life; however, the median number of NAVA ventilation episodes was three, meaning that most of the infants also needed other invasive respiratory modes.…”
Section: Discussionmentioning
confidence: 99%
“…NAVA is a ventilatory mode that delivers synchronized assisted ventilation, proportional to the respiratory drive, using the electrical activity of the patient's diaphragm (EAdi) 6 . NAVA is already being used in newborns, especially premature ones, and has been shown to have many benefits: lower peak inspiratory pressure (PIP), lower work of breathing (WOB), better patient–ventilator interaction, and better gas exchange 7–13 . The use of NAVA was also associated with a reduction of sedation, 14 which probably impacts the hemodynamic status and risk of withdrawal in infants.…”
Section: Introductionmentioning
confidence: 99%
“…NAVA can be used as an invasive (via an endotracheal tube) or a non-invasive (via a nasal mask or nasal prongs: NIV-NAVA) ventilation mode [1]. Several clinical studies have shown that NAVA and NIV-NAVA are feasible, safe and effective in preterm neonates [2][3][4][5][6]. The NAVA level is the factor that converts the Edi signal in a proportional pressure.…”
Section: Introductionmentioning
confidence: 99%